(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
Mangrove forest is one type of coastal forest that forming an ecosystem, in which its root system can dissipate waves, especially for coastal protection. Nevertheless, the effectiveness of mangrove forest for dissipating wave is still unclear, especially for short wave such as regular wave. The purpose of this research is to analyze the effectiveness of mangrove forest in dissipating regular wave by using numerical simulation approach. To simulate short waves accurately, one should choose a dispersive wave model. In this research, we choose a Boussinesq type of model, i.e. the Variational Boussinesq (VB) model as the wave model. Here, the Finite Volume method is chosen as the numerical implementation of model, in a staggered grid scheme. The dissipation process by the mangrove forest is modelled as a bottom dissipation that equivalent with a Manning’s coefficient that is derived from physical experiment. The resulting numerical implementation is then validated with experimental data from hydrodynamic laboratory which gives relatively accurate results. To analyze the effectiveness of dissipation by mangrove forest, we perform various simulation scenarios with various length of mangrove forest. From the results, it is shown that to obtain a 67% wave height dissipation of regular wave, we require at a mangrove forest with length as least 2 times the length incoming regular wave.